Association of Fetal Heart Rate Tracing with Adverse Neonatal Outcomes at 32.0 to 36.6 Weeks - Cortes, Christina; Cagino, Kristen A; Roberts, Aaron W; Wiley, Rachel; Patel, Shareen; Zullo, Fabrizio; Mendez-Figueroa, Hector; Chauhan, Suneet P (American Journal of Perinatology)
Objective: To determine if patterns of fetal heart rate tracings (FHRT) were associated with an increased rate of composite adverse neonatal outcomes (CANO) among preterm deliveries at 32.0 – 36.6 weeks. Methods: This was a retrospective review of intrapartum FHRT between 20 to 120 min before birth, among non-anomalous singletons delivered at 32.0 to 36.6 weeks. The study was conducted at a Level IV maternal center during a consecutive 15-month period. Obstetricians reviewing FHRT were blinded to the maternal characteristics, intrapartum course, and neonatal outcomes. FHRT patterns were categorized based on time spent in the final two hours before delivery (<50% vs. ≥50%). The primary outcome was the CANO which included any of the following: 5-minute APGAR less than 7, mechanical ventilation >6 hours, umbilical artery pH <7.00, bronchopulmonary dysplasia, interventricular hemorrhage, necrotizing enterocolitis, neonatal seizures, neonatal confirmed sepsis, hypoxic ischemic encephalopathy, birth injury, meconium aspiration syndrome, or neonatal death. Results: Of 5,160 patients, 672 (13%) met the inclusion criteria. CANO occurred in 57 (8.5%) newborns. Overall FHRT patterns that differed significantly between those without versus with CANO included minimal variability (8.8% versus 19.3%, p=0.01, PLR 2.2 [positive likelihood ratio], PPTP 17% [positive post-test probability]), moderate variability (76.4% versus 52.6%, p<0.001, NLR 2.01 [negative likelihood ratio], NPTP 15.7% [negative post-test probability]), accelerations (58.4% versus 40.4%, p=0.009, NLR 1.43, NPTP 11.7%), and severe variable decelerations ( 3.5% p=0.003, PLR 10.79, PPTP 50.1%). Category III FHRT pattern was also associated with an increased post-test probably of CANO (0.3% vs 1.8%, p=0.12, PLR 5.39, PPTP 27%). Conclusion: While moderate variability and accelerations were associated with significantly lower likelihood of CANO among newborns delivered at 32.0 to 36.6 weeks, minimal variability and severe variable decelerations were significantly more common in preterm newborns with CANO.